Preparation and Properties of Corrosion-Resistant Coatings From Waterborne Polyurethane Modified Epoxy Emulsion - Zhang, Jianjun; Huang, Hao; Ma, Jun; Huang, Luyao; Huang, Lu; Chen, Xiaohua; Zeng, Hao; Ma, Sude (Frontiers in Materials, 2019)
Corrosion of metal products can seriously affect their reliability. The application of coatings is the most widely used method of corrosion protection due to the desire for easy application and low cost. Most of the present corrosion-resistant coatings are solvent coatings. Due to the high content of volatile organic compounds, the use of solvent coatings is restricted. Currently, the corrosion resistance of waterborne coatings is much lower than that of solvent coatings, so research and development of waterborne corrosion-resistant coatings are necessary and valuable. A corrosion-resistant waterborne polyurethane modified epoxy (WPUME) emulsion was prepared and characterized by Fourier transform infrared (FTIR) spectra, transmission electron microscopy, and thermal gravimetric analysis. The particle size, dispersion, and solid content of the emulsion were tested by laser-scattering equipment and a weighing method. Coatings were prepared based on the emulsion, and the properties (i.e., water absorption rate, salt spray resistance, and flexibility) of the coatings were tested by the standard method, respectively. Results show that the synthesis reaction accords well with the molecule design, and the average diameter of the particles in the emulsion is 100 nm approximately. The cured coating, which is coated on tinplate sheets, has good flexibility and can withstand the salt spray test for more than 60 days (i.e., 1,440 h). The emulsion has many potential practical applications in the protection of metal materials.